The Electoral System of the Republic of Italy - Kalantaryan, Edgar (YSU Journal of International Affairs, 2022)
In a number of post-war European countries, reforms were carried out to modernize and democratize public administration. The Italian Republic was not an exception. Throughout its history, in the course of constitutional institutions, it had gone through the constitutional monarchy, totalitarian fascist dictatorship, thus forming the most democratic constitution of the post-war Europe. The Italian Constitution clearly regulates the system of government, which is based on the principle of separation of powers. All this is regulated by the regulation of electoral systems. They have been changed quite often in Italy, showing a certain weakness. This is conditioned not only by unstable intra-parliamentary legal-political structures, but in some cases even by the disagreements of political parties.